Analysis on productivity improvement, using lean manufacturing concept. (2021) - Joseph, R. Edwin; Kanya, N.; Bhaskar, K.; Xavier, J. Francis; Sendilvelan, S.; Prabhahar, M.; Kanimozhi, N.; Geetha, S.
Abstract: This work reports the testing and analysis carried out in a firm located in Chennai, which supplies timing belt to original equipment manufacturers (OEM). The objectives of this paper are to improve the productivity in the work floor by using the lean manufacturing concept. The introduction of Overall Equipment Efficiency (OEE) in the manufacturing process identifies the complex issues in the working process which affects the productivity. The tool which is used for the evaluating the parameters affecting productivity is cycle time study. After the complete study from cycle time study a new set of process were implemented and it has been compared with previous results hence the productivity is increased. In Previous method, the Productivity ranges from 7.32 to 7.97 slabs per hours. By Implementing the Standardize the Cycle time variation the productivity is improved to 9.1 slabs per hours with an Overall Improvement of production of 19.1% in a day. The cycle time study was again carried out and listed in table 4 after the implementation of Phase 1, 2, and 3 the process time activity has been improved from 392 s to 317 s.